Adherence to oral anticoagulation in a Belgium atrial fibrillation population measured by a medical event monitoring system. (19th May 2022) - Knaepen, L; Delesie, MD; Vijgen, J; Dendale, P; Ector, J; Desteghe, L; Heidbuchel, H
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): The AF-EduCare study is a project supported by the Fund for Scientific Research, Flanders (T002917N). The AF-EduApp study is supported by an BMS/Pfizer European Thrombosis Investigator Initiated Research Program (ERISTA) grant. Background: Treatment with oral anticoagulation (OAC) is one of the main pillars in the management of atrial fibrillation (AF). Therapy adherence to both VKA and NOAC is important. Education and intake monitoring are recommended to improve therapy adherence. Purpose: The main purpose of this project was to evaluate the effect of personalized follow-up strategies on therapy adherence to OAC in AF patients. Methods: In a multicentre, Belgian randomized controlled trial, the AF-EduCare/AF-EduApp study, the effect of different personalized education strategies (i.e. in-person, online or app-based education) is evaluated on clinical outcome parameters of AF patients compared to standard care (SC). One of the outcome parameters is therapy adherence to OAC. During the first 3 months of the trial, patients' adherence to NOAC or VKA was measured with the Electronic Medication Event Monitoring System (MEMS). The MEMS cap fits on a medication bottle and registers the date and time of every bottle opening. Regimen adherence was defined as the the number of days with the correct number of openings according to the specific OAC regimen divided by the total number of monitored days. As dabigatran has to be stored in the original package to protect it from moisture and VKAs have a variable scheme between patients, a proxy-medication (i.e. another oral drug that needed to be taken once or twice daily and on the same moment of the day as dabigatran or VKA) was chosen to measure medication adherence. Patients in the education groups received a MEMS cap with LCD screen providing direct feedback by showing the number of openings within 24h. A small sample of the SC group also received a MEMS cap as controls, but without LCD screen to minimally trigger these patients. Results: A total of 593 AF patients underwent adherence monitoring, of which 514 (86.7%) in the intervention group and 79 (13.3%) in the SC group. The mean age was 70.1±7.7 years, mean time since AF diagnosis was 5.8±6.9 years, and mean CHA2DS2-VASc score was 3.2±1.5. Overall adherence was high: 94.8% of the patients had an adherence >80% and 80.9% had an adherence >90%. A small but significant difference in adherence was observed between the intervention groups and the standard care group (intervention group 97% (5-100); SC 96%(24-100); p=0.024; Figure1). Also between the four study groups a significant difference was seen (in-person 97% (93.5-99); online 98% (94-100); app-based 98% (92-99); p=0.049) driven by a significant difference between the online and SC group (p=0.009). Conclusion: Overall adherence to OAC in all study groups and even in SC was high. The high adherence percentage in the SC group could be related to the Hawthorne effect of using the MEMS. Nevertheless, electronic monitoring and targeted education slightly improved therapy adherence further in the intervention groups.